TET Enzymes and 5-Hydroxymethylcytosine in Neural Progenitor Cell Biology and Neurodevelopment - MacArthur, Ian C.; Dawlaty, Meelad M. (Frontiers in Cell and Developmental Biology, 2021)
Studies of tissue-specific epigenomes have revealed 5-hydroxymethylcytosine (5hmC) to be a highly-enriched and dynamic DNA modification in the metazoan nervous system, inspiring interest in the function of this epigenetic mark in neurodevelopment and brain function. 5hmC is generated by oxidation of 5-methylcytosine (5mC), a process catalyzed by the ten-eleven translocation (TET) enzymes. 5hmC serves not only as an intermediate in DNA demethylation but also as a stable epigenetic mark. Here, we review the known functions of 5hmC and TET enzymes in neural progenitor cell biology and embryonic and postnatal neurogenesis. We also discuss how TET enzymes and 5hmC regulate neuronal activity and brain function and highlight their implications in human neurodevelopmental and neurodegenerative disorders. Finally, we present outstanding questions in the field and envision new research directions into the roles of 5hmC and TET enzymes in neurodevelopment.